PSYCHOLOGICAL CONFLICT AND CHARACTER COMPLEXITY IN ASADBEK’S PERSONA IN TOHIR MALIK’S «SHAYTANAT» (Proceedings of International Educators Conference, 2024)
This article delves into the intricate psychological conflicts and character complexities portrayed in the persona of Asadbek, the central figure in Tohir Malik’s renowned novel «Shaytanat». The novel, despite being crafted in the mid-20th century, continues to captivate its readership through its profound narrative and character analysis. The focal point of this study is the duality of Asadbek’s nature, oscillating between his ruthless criminal persona and his intrinsic human qualities, such as his roles as a caring father, a devoted friend, and a loving son. Through a meticulous examination of Asadbek’s inner turmoil, moral dilemmas, and emotional struggles, this article seeks to unravel the layers of his complex character. The analysis is grounded in literary theories that explore the symbiotic relationship between character development and psychological depth, thereby providing a comprehensive understanding of the multifaceted dimensions of Asadbek’s character in «Shaytanat».